Simultaneous Phytochrome-controlled Promotion and Inhibition of Arginine Decarboxylase Activity in Buds and Epicotyls of Etiolated Peas - Dai, Yao-Ren (1981)
The specific activity of arginine decarboxylase (ADC; l-arginine carboxylase; EC 4.1.1.19) rises steadily over an 8 hour experimental period in the growing buds and subapical epicotyl internodes of 6-day-old totally etiolated pea seedlings. Treatment with red light (R) completely annuls this rise in epicotyls but increases it in buds, thus paralleling the opposite effects of R on the growth of these two organs. Far red light (FR) reverses both effects of R on ADC and is, in turn, reversed by R, indicating phytochrome control. Effects in both organs are clearly seen within 2 hours. By 6 hours after R, the post-irradiation rise in ADC specific activity in buds is 3 times greater than that of the dark controls. Over the same period, ADC specific activity in epicotyls is inhibited by 56% relative to dark controls, reflecting zero net change after R and a continued rise in the dark. Cycloheximide inhibits the rise in ADC activity in both rapidly growing organs (epicotyls in dark and buds after R) but is without effect in both slower growing organs. Actinomycin D inhibits only in dark grown epicotyls, whereas chloramphenicol produces no inhibition in any system tested. ADC is the first enzyme to show a two-way, organ-specific response to phytochrome conversion from Pr to Pfr. This finding is discussed in relation to the growing evidence that polyamines formed from arginine may be important growth regulators in plants, as well as in microbial and animal cells.